Laser guided ionic wind - Shengzhe Du (Nature Portfolio, 2018)
Abstract We report on a method to experimentally generate ionic wind by coupling an external large electric field with an intense femtosecond laser induced air plasma channel. The measured ionic wind velocity could be as strong as >4 m/s. It could be optimized by increasing the strength of the applied electric field and the volume of the laser induced plasma channel. The experimental observation was qualitatively confirmed by a numerical simulation of spatial distribution of the electric field. The ionic wind can be generated outside a high-voltage geometry, even at remote distances.